Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Siswa - Nur Rahmatan Mursalin; Husnul Khotimah Rustam (JITU Jurnal Ilmiah Tarbiyah Umat, 2026)
Background of study: Low student engagement in Pancasila learning can impact learning outcomes. The inquiry learning model is seen as capable of increasing student engagement in the learning process. Aims and scope of paper: The objective of this study was to improve student learning processes and outcomes through the application of the inquiry learning model. The subjects were all 18 fourth-grade students at Public Elementary School 46 in Parepare City. Methods: This research is a Classroom Action Research (CAR) which uses a quantitative approach. Result: The results of the study showed that there was an increase in cognitive learning outcomes, namely students were able to implement Pancasila values ​​in all cycles guided by teachers. In the affective domain, students were able to be more independent, sensitive and empathetic to friends who were experiencing difficulties. Quantitatively, I. Student activity also increased from 66.04% in cycle I to 83.64% in cycle II. The average value of students from their learning outcomes was 95. Teacher activity increased from 61.11% in cycle I to 88.88% in cycle II. Conclusion: Thus, it can be concluded that the application of the inquiry learning model is able to improve the learning outcomes of fourth grade students at SDN 46, Parepare City.